Astaxanthin's anti-angiogenic Effects: Network pharmacology and functional validation in endothelial cells - Barizi, Anis Zuhaida Mamnun; Abdullah, Muhammad Nazrul Hakim; Lim, Vuanghao; Yong, Yoke Keong (Elsevier, 2025)
Angiogenesis, the formation of new blood vessels from existing ones, is crucial for tumor growth and metastasis. Anti-angiogenic agents are thus a promising therapeutic strategy for cancer. Astaxanthin (ATX), a reddish pigment from the xanthophyll family of carotenoids, may be an effective anti-angiogenic agent due to its notable antioxidant and anti-inflammatory properties. This study aims to investigate the anti-angiogenic effects of ATX on VEGF-induced human umbilical vein endothelial cells (HUVECs). We employed in-silico and in-vitro approaches to evaluate ATX's anti-angiogenic potential. Cytotoxicity assays used concentrations ranging from 50 to 3.125 μM, while other assays utilized concentrations from 25 to 6.25 μM. Network pharmacology identified four hub genes—RXR, CCND1, CDK1, and HDAC1—as key ATX targets against angiogenesis. Molecular docking revealed significant binding affinities of ATX with seven receptors, notably VEGFR2. In vitro, ATX exhibited a dose-dependent cytotoxic effect on HUVECs (IC50 = 75.09 μM), reducing cell viability by 33 % at 50 μM (p<0.05). Additionally, ATX inhibited cell proliferation over 72 h, with significant decreases in VEGF-induced HUVEC viability (p<0.05). The scratch wound healing assay demonstrated ATX's anti-migratory effect, with a 20 % migration rate at 25 μM over 8 h (p<0.05). Lastly, ATX suppressed tube formation over a 6-h period, significantly reducing average tube length (p<0.05). In conclusion, ATX exhibited significant anti-angiogenic properties through cytotoxicity, inhibition of proliferation, migration, and tube formation in VEGF-induced HUVECs. These findings provide a strong foundation for further research on ATX's potential therapeutic application in angiogenesis-related disorders, including cancer.